2022
DOI: 10.1111/1440-1681.13740
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of inflammatory and nutritional indexes among advanced NSCLC patients receiving PD‐1 inhibitor therapy

Abstract: Though immunotherapy has to some extent improved the prognosis of patients with advanced non‐small cell lung cancer (NSCLC), only a few patients benefit. Furthermore, immunotherapy efficacy is affected by inflammatory and nutritional status of patients. To investigate whether dynamics of inflammatory and nutritional indexes were associated with prognosis, 223 patients were analysed retrospectively. The inflammatory indexes of interest were neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…16 studies with 2378 patients(16-18, 21,22,27,30,32,34,36,37,39,41,42,44,47) showed an association between the SII and PFS in NSCLC. Heterogeneity was signi cant (I 2 = 83.1%, P < 0.001), and a random-effects model was performed.…”
Section: Sii and Pfs In Nsclcmentioning
confidence: 99%
See 2 more Smart Citations
“…16 studies with 2378 patients(16-18, 21,22,27,30,32,34,36,37,39,41,42,44,47) showed an association between the SII and PFS in NSCLC. Heterogeneity was signi cant (I 2 = 83.1%, P < 0.001), and a random-effects model was performed.…”
Section: Sii and Pfs In Nsclcmentioning
confidence: 99%
“…Numerous studies have investigated the prognostic signi cance of SII in NSCLC, but their results have been inconsistent . While some studies have identi ed SII as a crucial prognostic factor for NSCLC, others have not supported this view (41)(42)(43)(44). For instance, Soykut et al found that elevated SII was an independent prognostic marker for overall survival (OS) in NSCLC patients treated with chemoradiotherapy (hazard ratio [HR], 1.63; 95% con dence interval [CI], 1.18-2.04; p < 0.001) (36).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation induces leukocytosis, and the systemic immune-inflammatory index (SII), neutrophilto-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR) can serve as inflammatory biomarkers and have been validated as diagnostic predictors in patients with lung and liver cancers receiving immunotherapy. 24,25 Therefore, we investigated the effects of inflammatory biomarkers (SII, PLR, NLR, and LMR) on TLS abundance and maturity of TLSs. We also compared the predictive values of these inflammatory parameters, TLSs, and the combination of inflammatory parameters with TLSs for immunotherapy efficacy in patients with NSCLC receiving neoadjuvant immunochemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The systemic immune inflammatory index (SII) is based on a prognostic score of inflammation and immunity, which is calculated as platelet count*neutrophil count/lymphocyte count. Inflammation induces leukocytosis, and the systemic immune‐inflammatory index (SII), neutrophil‐to‐lymphocyte ratio (NLR), lymphocyte‐to‐monocyte ratio (LMR), and platelet‐to‐lymphocyte ratio (PLR) can serve as inflammatory biomarkers and have been validated as diagnostic predictors in patients with lung and liver cancers receiving immunotherapy 24,25 …”
Section: Introductionmentioning
confidence: 99%